Quantifying FDI’s Effects on GDP and Unemployment: Evidence from North Macedonia - Malchev, Bojan; Trpeska, Marina; Minovski, Zoran (Faculty of Economics-Skopje, Ss. Cyril and Methodius University in Skopje, 2025)
This paper examines the impact of foreign direct investment (FDI) on economic growth and unemployment in North Macedonia over the period 2014–2023. North Macedonia, a small post-transition economy with historically high unemployment, has actively pursued FDI as a development strategy. Using annual data and econometric analysis (stationarity tests, Pearson correlations, and OLS regressions in SPSS), we test four hypotheses about FDI’s relationship with GDP growth and unemployment. The results indicate a strong positive association between FDI inflows and real GDP growth and a significant negative association between FDI and the unemployment rate. In particular, higher FDI is correlated with faster GDP growth and lower unemployment, supporting the view that FDI can be a catalyst for economic development. Regression analysis further suggests that FDI has a statistically significant positive effect on GDP growth and a negative effect on unemployment, even when accounting for the growth-employment link. These findings confirm the optimistic hypothesis that FDI inflows drive macroeconomic improvements in North Macedonia. However, complementary factors (institutional quality, human capital) are crucial for maximizing FDI benefits. The paper concludes with policy implications, emphasizing the need to attract quality FDI and strengthen domestic absorptive capacities to ensure sustainable growth and job creation.
Keywords: Foreign direct investment; Economic growth; Unemployment; North Macedonia; Transition economy